Experimental Evaluation of Wöhler Curve for Mild Steel Plates Manufactured In Nepal - Dixit, Subrat Mani; Dura, Hari Bahadur; Dulal, Hemanta (Journal of Advanced College of Engineering and Management, 2022)
This research work was carried out to explore the fatigue behavior of Mild Steel Plates manufactured in Nepal and determine the Wöhler Curve of the plates by preparing test specimens and conducting fatigue experiment of the specimens in the rotating cantilever bending fatigue test machine. The laboratory data thus obtained were plotted to generate the Wöhler Curve of the material. Along with the curve the Basquin’s Coefficients and Endurance limitup to 106 cycles were determined. Specimen was designed in accordance to ASME E 466-15 and the machining was done in accordance to IS 1075-1985 and then was subjected to various different loads. Exploratory tensile test of the material was also done in order to find out the proportion of the applied load with respect to the ultimate strength of the material. Surface crack was also inspected.Micro void coalescence and Micro cleavage formations were noticed in the fractured section.